Spiritual Mandate to Zero Waste: Türkiye and Indonesia’s Mutual Ecological Transformation through Nursi’s Eco Tawhīd - Moh. Isom Mudin; Nabila Huringiin; Mohamed Hedi Ouannes; Tuğba Türkoğlu (Jurnal Ushuluddin, 2026)
This study examines how Bediüzzaman Said Nursi's concept of Eco-Tawḥīd; a theocentric framework integrating Khilafah (vicegerency), al-Amānah al-Kubrā (the Great Trust), and Qānūn al-Ṭuhr (the Law of Cleanliness as a manifestation of the divine name Al-Quddūs) can serve as a spiritual bridge for mutual ecological transformation between Türkiye and Indonesia. Despite zero‑waste policies (Türkiye's Zero Waste Project and Indonesia's Presidential Regulation No. 109/2025), both nations face persistent implementation gaps. Using a qualitative comparative document analysis of ministry reports, the Risale‑i Nur, fatwas, and civil society initiatives (Nurcu movement in Türkiye; Muhammadiyah, NU, MUI, Eco Masjid in Indonesia), the study finds that Türkiye excels in execution 27.2% waste recovery, 65.2 billion TL savings, nationwide education, but embeds Nursian ethics only implicitly. Indonesia, conversely, articulates Khilafah explicitly in state ecotheology and fatwas, yet suffers from systemic failure: 60% unmanaged waste, 343 open‑dump landfills, and 48% household open burning. The study proposes a mutual‑learning bridge grounded in Nursi's eco-Tauhid: Indonesia can adopt Türkiye's phased roadmap, incentive systems (Z‑card, mobile collection), and public campaigns; Türkiye can embrace Indonesia's regulatory innovation (waste‑to‑energy with 30‑year investment tariffs) and formal theological grounding of Khilafah. This synthesis reframes zero waste not as a technical problem but as a sacred stewardship imperative, transforming both nations from crisis management to spiritual‑ecological governance.